Impact of a single session of hyperbaric oxygen therapy on the healthy retina - Demir, Nur; Sumen, Selin Gamze; Kayhan, Belma (Frontiers in Ophthalmology, 2025)
BackgroundHyperoxia induced by hyperbaric oxygen therapy (HBOT) may lead to retinal vasoconstriction and the generation of reactive oxygen species. This study aims to investigate the effects of a single session of HBOT on the healthy retina using full-field electroretinography (ffERG) and spectral-domain optical coherence tomography (SD-OCT).MethodsTwenty patients diagnosed with either sensorineural hearing loss or avascular necrosis, all of whom had an indication for HBOT, were included in the study. A comprehensive ophthalmologic examination, along with ffERG and SD-OCT assessments of the retinal layers and choroid, were performed both before and within 24 hours after the first HBOT session.ResultsThe mean age of the participants was 43.2 ± 11.4 years (range, 18–66 years). A statistically significant difference was observed only in the scotopic 0.01 ERG b-wave amplitude before and after HBOT (p = 0.029). The retinal pigment epithelium in the 3-mm nasal subfield of the Early Treatment Diabetic Retinopathy Study (ETDRS) grid demonstrated a statistically significant thickening after the first HBOT session (p = 0.023).ConclusionA single session of HBOT induced an acute alteration in rod–bipolar cell function, as evidenced by impaired electrophysiological responses. Additional studies are necessary to clarify the duration and potential reversibility of the observed electrophysiological impairment.